Biomimetic freestanding microfractals for flexible electronics - Barua, Amit; Gogoi, Rituporn; Reddy, Pulikanti Guruprasad; Jolaiy, Saman; Bodaghi, Mahdi; Laukkanen, Timo; Speck, Thomas; Sariola, Veikko; Sharma, Vipul (Springer Science and Business Media LLC, 2025)
The microfractals of leaf skeletons can be effective substrates for flexible electronics due to their high surface-to-volume ratio, transparency, breathability and flexibility. The challenge lies in replicating these fractal surfaces at the microscale in a way that is scalable, freestanding, and integrable with various materials. In this study, we present a novel method for the biomimetic microfabrication of leaf-skeleton-based fractal surfaces. We utilized a modified electrospinning method, replacing the fiber collector with a metalized biotic collector to replicate the microstructures. The biomimetic microfractals demonstrated ~90% replication accuracy, >80% transparency, good stretchability, and breathability, and were freestanding. The method is versatile, allowing for the use of a wide range of polymers in biomimetic microfabrication. For application in flexible electronics, biomimetic conductive fractal patterns (BCFP) were fabricated by immobilizing Ag Nanowires (AgNW) using a simple spray-based method. The BCFP exhibited high conductivity with sheet resistances <20 Ω sq–1 while maintaining good transparencies. The BCFP adheres conformally to human skin, acting as an electronic skin (e-skin). To demonstrate the application, the BCFP was used to fabricate a tactile pressure sensor. In addition to their excellent transparency at low sheet resistances, stretchability, moisture resistance, and tight conformal bonding with the target surface, the BCFP also allows the evaporation of perspiration, making them suitable for long-term use as epidermal sensors. The application of BCFP in advanced bionic skin was demonstrated through gesture monitoring experiments.